2007
DOI: 10.1038/sj.jcbfm.9600590
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reactivity of Cerebral Capillaries

Abstract: The spatiotemporal evolution of cerebral microcirculatory adjustments to functional brain stimulation is the fundamental determinant of the functional specificity of hemodynamically weighted neuroimaging signals. Very little data, however, exist on the functional reactivity of capillaries, the vessels most proximal to the activated neuronal population. Here, we used two-photon laser scanning microscopy, in combination with intracranial electrophysiology and intravital video microscopy, to explore the changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
224
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(249 citation statements)
references
References 42 publications
21
224
4
Order By: Relevance
“…31) and 3.7 to 4.1 mm (ref. 32) under normocapinia to hypercapnia, respectively. Therefore, we considered these effects of the hypoventilation were minimal in our experimental conditions.…”
Section: Vascular Sprouting and New Connectionmentioning
confidence: 98%
See 1 more Smart Citation
“…31) and 3.7 to 4.1 mm (ref. 32) under normocapinia to hypercapnia, respectively. Therefore, we considered these effects of the hypoventilation were minimal in our experimental conditions.…”
Section: Vascular Sprouting and New Connectionmentioning
confidence: 98%
“…A closed cranial window provided consistent microvessel and astrocyte structures over 2 to 7 weeks after the surgical procedures under normoxia conditions, 21 indicating the minimum effects because of inflammation resulting from the craniotomy. Previous studies for vasodilation to transient hypercapnia 31,32 and neural activation 33,34 showed that the diameter of the parenchymal capillary was relatively stable, with at most a 10% change. Thus, the mechanism of vasodilation induced through chronic hypoxia differs from the previously known responses.…”
Section: Vascular Sprouting and New Connectionmentioning
confidence: 99%
“…Several authors have noted a significant capillary vasodilation (Villringer et al, 1994;Hutchinson et al, 2006;Vanzetta et al, 2005;Stefanovic et al, 2008). As pointed out by Stefanovic et al (2008), in the more recent of these studies, "very little data, however, exist on the functional reactivity of capillaries."…”
Section: Blood Flow Control and Passive Responsesmentioning
confidence: 99%
“…As pointed out by Stefanovic et al (2008), in the more recent of these studies, "very little data, however, exist on the functional reactivity of capillaries." Using two-photon laser scanning microscopy, these authors estimated the contribution of the capillaries to the total stimulation-induced CBV changes and concluded that less than 1/5 (~18%) of the total blood volume increase is occurring on the level of capillaries.…”
Section: Blood Flow Control and Passive Responsesmentioning
confidence: 99%
“…The notion of a propagating hemodynamic wave, however, can be substantiated by the observation that the estimated wavefront velocities are in line with capillary blood velocities in rodents, i.e. in the order of 1 mm/s (Stefanovic et al, 2008). …”
Section: Resultsmentioning
confidence: 99%